2018
DOI: 10.1002/celc.201801448
|View full text |Cite
|
Sign up to set email alerts
|

New Insights for the Abuse Tolerance Behavior of LiMn2O4 under High Cut‐Off Potential Conditions

Abstract: The further development of lithium-ion batteries is often desired to obtain higher capacities by charging to higher potentials. However, such a high potential (> 4.3 V) will inevitably result in capacity loss of the LiMn 2 O 4 cathode material over numerous cycles. In this work, degradation mechanisms of LiMn 2 O 4 electrode cycled at different charge cut-off potentials (4.4, 4.5, 4.6, 4.7, and 4.8 V vs. Li/Li + , respectively) have been investigated. It is found that the capacity degraded seriously after agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Dissolution of manganese was observed for a variety of cathode materials [16, 17, 20, 21, 28–33]. In addition to dissolution mechanisms like corrosion or structural deformation, dissolution by disproportionation reaction of surficial Mn 3+ to Mn 4+ and soluble Mn 2+ is mainly reported in the literature [7, 17, 18, 20, 21, 29, 30, 3436]. Several more recent studies found dissolved manganese to be mainly in oxidation state +3 not in +2, which is in contradiction to established reports.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolution of manganese was observed for a variety of cathode materials [16, 17, 20, 21, 28–33]. In addition to dissolution mechanisms like corrosion or structural deformation, dissolution by disproportionation reaction of surficial Mn 3+ to Mn 4+ and soluble Mn 2+ is mainly reported in the literature [7, 17, 18, 20, 21, 29, 30, 3436]. Several more recent studies found dissolved manganese to be mainly in oxidation state +3 not in +2, which is in contradiction to established reports.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is reported that the increasing cut-off potential results the higher Li + ion extraction from cathode. [12,13] Hence, further enhanced capacity of NMC can be obtained by increasing its upper cut-off potential. But at higher potential, the use of flammable liquid electrolyte arises the safety problem.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on these organic fragments, and omit inorganic CEI components like LiF and Li w P x O y F z , related to PF − 6 decomposition. Such inorganic species are present [12][13][14]40,41 but neither release CO 2 gas nor have been predicted to be oxidized at any reasonable voltages. Indeed, PF − 6 decomposition products have been suggested to partially passivate LNMO.…”
Section: Introductionmentioning
confidence: 99%